Commodity Systems Assessment Methodology of Postharvest Losses in Vegetable Amaranths: The Case of Tamale, Ghana - Mildred Osei-Kwarteng; Joseph Patrick Gweyi-Onyango; Gustav Komla Mahunu (International Journal of Agronomy, 2017)
A semistructured questionnaire based on the commodity system assessment methodology (CSAM) was used to determine postharvest losses in vegetable amaranths (VA). Fifty producers and retailers were randomly selected from five and four major VA producing areas and markets, respectively, and interviewed. Data obtained were subjected to descriptive statistical analyses. The survey revealed that absence of laws, regulation, incentives, and inadequate technical information affected the production of VA. The utmost preproduction challenge was poor quality seeds with poor seed yield (35%), low viability (19%), and nontrueness (46%). It was noted that some cultural practices including planting pattern and density, irrigation, and fertiliser use had effects on postharvest losses. Some postharvest practices used were cleaning with water, trimming, sorting, and grading. Usually the produce was transported to marketing centers by cars and motor cycle trailers. Generally poor temperature management after harvest was a big challenge for the postharvest handling of VA. The potential of vegetable amaranths as a commodity in the study area can be enhanced by providing the necessary institutional support, incentives, and use of good management practices along the value chain. An interdisciplinary approach and quantification of losses along the chain are recommended for any future study.